Jacques Derrida and zoomorphism: an inquiry - Michta, Kamil (Przestrzenie Teorii, 2018)
The article discusses zoomorphism as part of the anthropocentric discourse aimed at establishing human dominance over animals. Basing on Jacques Derrida’s 1997 paper “The Animal That Therefore I Am (More to Follow),” the article approaches anthropomorphism and zoomorphism as culturally sanctioned ways of misrepresenting animality and shaping human attitudes towards real-life animals. A symptom of the misrepresentation is the gap between animals and their linguistic denotations. The specific aim of the article is to demonstrate that zoomorphism as used in everyday language conserves the human-centered vision of the world by ignoring the differences between individual animals. The discussion concludes by arguing that zoomorphism can be remedied by the individualizing aspects of anthropomorphism.